Pengalaman Pengguna Pada Platform Magang : Pengembangan Dan Evaluasi Melalui Pengujian Berbasis UEQ - Massaty, Muhammad Hassan; Andrian, Dimas Pamilih Epin; Fahrurozi, Slamet Kurniawan (Jurnal Ilmiah SINUS, 2025)
This study investigates the development and evaluation of the User Experience (UX) of a web-based internship platform aimed at enhancing communication and collaboration between students and campus staff. The platform was developed using a User-Centered Design (UCD) approach, incorporating user feedback at each stage of the design process. Prior to system development, interviews were conducted with both students and campus staff to identify existing challenges. The findings revealed that 80% of students encountered difficulties in accessing up-to-date internship information, 70% struggled to track the progress of their applications, and 60% reported insufficient feedback from industry partners or campus coordinators. Additionally, 60% of campus staff faced challenges in managing communication and providing timely updates on internship applications. Based on these insights, the platform was designed to address these issues. UX evaluation was performed using the User Experience Questionnaire (UEQ), assessing dimensions of attractiveness, usability, efficiency, and emotional satisfaction. The results demonstrated that the platform successfully met user expectations in terms of accuracy and novelty; however, the stimulation dimension requires further refinement. This study underscores the significance of adopting a UCD approach in the development of educational platforms and offers valuable insights for future research on web-based platforms in educational contexts.